2003
DOI: 10.1002/dvdy.10326
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β3–dependent SMAD2 phosphorylation and inhibition of MEE proliferation during palatal fusion

Abstract: Transforming growth factor (TGF) -␤3 is known to selectively regulate the disappearance of murine medial edge epithelium (MEE) during palatal fusion. Previous studies suggested that the selective function of TGF-␤3 in MEE was conducted by TGF-␤ receptors. Further studies were needed to demonstrate that the TGF-␤ signaling mediators were indeed expressed and phosphorylated in the MEE cells. SMAD2 and SMAD3 were both present in the MEE, whereas SMAD2 was the only one phosphorylated during palatal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 28 publications
(37 reference statements)
2
50
1
Order By: Relevance
“…4A) as a result of MEE seam formation (12 hr), then assume a similar expression level while approaching EMT (24 hr). Smad3 was determined to be absent in each stage (data not shown), confirming that in the palate system, Smad2 is the necessary R-Smad for EMT (Cui et al, 2003). Validation of the expression of Smad2, Smad3, Smad4, and LEF-1 was performed by means of reverse transcriptase-polymerase chain reaction (RT-PCR; Fig.…”
Section: The Tgf-␤ Signaling Pathwaymentioning
confidence: 60%
“…4A) as a result of MEE seam formation (12 hr), then assume a similar expression level while approaching EMT (24 hr). Smad3 was determined to be absent in each stage (data not shown), confirming that in the palate system, Smad2 is the necessary R-Smad for EMT (Cui et al, 2003). Validation of the expression of Smad2, Smad3, Smad4, and LEF-1 was performed by means of reverse transcriptase-polymerase chain reaction (RT-PCR; Fig.…”
Section: The Tgf-␤ Signaling Pathwaymentioning
confidence: 60%
“…Further, the inhibition of TGF-␤3 results in a failure of plate fusion in vitro (Brunet et al, 1995), and the addition of TGF-␤3 to cultures of palatal shelves from TGF-␤3-deficient mice is able to reverse the phenotype completely (Kaartinen et al, 1997;Taya et al, 1999). TGF-␤3 also induces an epithelial-mesenchymal transdifferentiation of the MEE (Kaartinen et al, 1997;Sun et al, 1998), possibly by regulating the expression of MMPs (Blavier et al, 2001) and proteoglycans (Gato et al, 2002) by Smad2-dependent mechanisms (Cui et al, 2003). These findings have been confirmed recently by Dudas et al (2004), who showed that TGF-␤3-induced palatal fusion was mediated by the Alk-5/Smad pathway.…”
Section: (B) Palatogenesismentioning
confidence: 86%
“…Expression of one of the family members, transforming growth factor β 3 (TGFB3), is detected in the epithelial component of the vertical palatal shelf and peaks at day 14 to 14.5, just before immediate contact of the palatal shelves. Potential roles of TGFβ3 in palate formation have been demonstrated both in vitro (Sun and Vanderburg et al, 1998;Gato et al, 2002;Cui et al, 2003) and in vivo (Cui et al, 2003). Using a case-parent study design, Maestri el al.…”
Section: Transforming Growth Factor βmentioning
confidence: 99%